The vacuolar amino acid transport system is a novel, direct target of GATA transcription factors. Issue 3 (20th January 2021) - Sato, Akane; Kimura, Takumi; Hondo, Kana; Kawano-Kawada, Miyuki; Sekito, Takayuki
ABSTRACT: In Saccharomyces cerevisiae, Avt4 exports neutral and basic amino acids from vacuoles. Previous studies have suggested that the GATA transcription factors, Gln3 and Gat1, which are key regulators that adapt cells in response to changes in amino acid status, are involved in the AVT4 transcription. Here, we show that mutations in the putative GATA-binding sites of the AVT4 promoter reduced AVT4 expression . Consistently, a chromatin immunoprecipitation (ChIP) assay revealed that Gat1-Myc 13 binds to the AVT4 promoter. Previous microarray results were confirmed that gln3 ∆ gat1 ∆ cells showed a decrease in expression of AVT1 and AVT7, which also encode vacuolar amino acid transporters. Additionally, ChIP analysis revealed that the AVT6 encoding vacuolar acidic amino acid exporter represents a new direct target of the GATA transcription factor. The broad effect of the GATA transcription factors on the expression of AVT transporters suggests that vacuolar amino acid transport is integrated into cellular amino acid homeostasis. Graphical Abstract: